Finger Painting Dalam Mengembangkan Motorik Halus Anak Di Era Society 5.0 - Nurfaizah; Ulya Ainur Rofi’ah; Muhimmatul Choiroh (Institut Agama Islam Nahdlatul Ulama Tuban, 2024)
Early Childhood Education, or PAUD, is one setting that can support kids' development. This is what the Minister of Education's rule No. 145 of 2014, often known as the child development achievement standards, states. Finger painting was selected as a technique that can be utilized in RA, particularly in RA Sumbersari, to aid in the development of fine motor abilities in young children. The purpose of this research, which was conducted during the KBM (teaching and learning activities) phase, was to enhance early childhood fine motor development abilities. The purpose of this study is to outline RA Sumbersari Kowang Semanding's initiatives to foster children's creativity through finger painting mediums. This kind of study is qualitative descriptive, and it involves RA Sumbersari teachers. Interviews, documentation, and qualitative data analysis utilizing techniques for data reduction, display, and verification were used to gather the data. The activity's outcomes demonstrated that the RA kids were extremely animated and joyful during its execution. It also garnered attention, which helped boost the kids' motivation to learn. Following the activity, the RA kids continued to be even more engaged in their studies.